Water use, energy use efficiency and carbon footprint of transplanted rice (Oryza sativa) in response to surface drainage - CHOUDHARY, V K (The Indian Journal of Agricultural Sciences, 2018)
A field study was undertaken to determine the productivity, water use, energy efficiency, and carbon footprint under enforced surface drainage for 15 days at various growth stages of rice (Oryza sativa L.) during kharif 2011 and 2012. The continuous submergence improved the rice grain yield (3.41 t/ha) and straw yield (4.68 tonnes/ha) over the continuous drainage. The water-use was higher with continuous submergence (15350 m3) followed by alternate wetting and drying, whereas, the lowest water was used with continuous drainage (5400 m3). The continuous submergence consumed the highest total input energy (84.97 x 103 MJ/ha) and produced 1.23 fold higher output energy, 452.6 of human energy profitability and 0.04 kg/MJ of energy productivity than the continuous drainage. Alternate wetting and drying was the most energy efficient which produced the highest energy ratio (1.53) and energy productivity 0.53). However, the lowest energy intensiveness was noticed with continuous drainage. Similarly, alternate wetting and drying followed by continuous drainage had the lowest carbon footprint and carbon dioxide emission. Thus, submergence of 5-7 cm may be followed as per the availability of water, while, submergence may be avoided for 15 days at tillering under limited water to obtain optimum yield with better energy efficiency.